2020
DOI: 10.1088/1742-6596/1697/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

The composition modulation effect during spinodal decomposition of ZnxCd1-xTe solid solutions under conditions of energy resonance

Abstract: The Cahn-Hillard equation, previously obtained to describe the decomposition of metal solid solutions, is adapted to analyze the spinodal decomposition of A2B6 semiconductor solid solutions. The obtained differential equation is used to describe the spinodal decomposition of the ZnxCd1-xTe solid solution, which is synthesized under conditions close to the boundaries of absolutely unstable regions on the state diagram of the system. A quantitative description of the composition modulation effect that appears in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…In this article, it is presented in full the thermodynamic and mathematical model for the spinodal decomposition of A 2 B 6 ternary semiconductor solid solutions when the deposition occurs without the stabilizing effect of a massive substrate. The findings obtained refine and supplement the results presented in the paper [12].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this article, it is presented in full the thermodynamic and mathematical model for the spinodal decomposition of A 2 B 6 ternary semiconductor solid solutions when the deposition occurs without the stabilizing effect of a massive substrate. The findings obtained refine and supplement the results presented in the paper [12].…”
Section: Introductionsupporting
confidence: 88%
“…As a rule, the indicated parameter and its temperature dependence are found by processing the data on phase equilibria in the systems in accordance with the model of simple solutions in different approximations. Despite the limited experimental information on the state diagrams of Zn-Cd-Te systems, especially at the low-temperature interval, the solid-state interaction parameters reported in the literature do not contradict their physical meaning and correlate well with each other for A 2 B 6 systems [4,12]. Such a situation justifies the possibility of using the data from works [4,12] for modeling the process of spinodal decomposition of the solid solutions to be considered.…”
Section: Thermodynamics Of Spinodal Decompositionmentioning
confidence: 88%
See 1 more Smart Citation
“…The possibility of realizing such a situation in ternary and quaternary A 3 B 5 systems was analyzed in several theoretical works [3,[5][6][7][8][9]. The results of these theoretical studies were confirmed in the description of experimental data on composition modulation effect in A 3 B 5 ternary and quaternary solid solutions.…”
Section: Introductionmentioning
confidence: 94%
“…The use of the analytical method to describe this effect in ternary solutions made it possible to explain the appearance of micro-oscillations in the composition of the layers [3,5,6]. A direct numerical solution of the Cahn-Hilliard spinodal decomposition equation made it possible to show that the phenomenon of resonance between the mixing energy of the components and the energy of elastically deformed inclusions of a new solid phase into which the material decomposes is responsible [7][8][9]. This effect is responsible for a significant increase in the amplitude of oscillations in the composition of the material to a value that can be experimentally detected.…”
Section: Introductionmentioning
confidence: 99%